The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.ijo.0802591
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in a randomised placebo-controlled trial of sibutramine in obese patients with type II diabetes

Abstract: OBJECTIVE:We evaluated the effects of 12-month treatment with sibutramine 15 mg daily compared with placebo on healthrelated quality of life (HRQL) in obese type II diabetes patients. We examined the associations between the changes in HRQL and in weight, glycaemic control, and haemodynamic variables. We also explored the predictive value of HRQL and its changes early during treatment. DESIGN: A randomised clinical trial. The subjects were enrolled in a 2-week single-blind run-in period with a modestly hypocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 33 publications
1
37
0
2
Order By: Relevance
“…In 16 studies, participants were obtained from random or all-inclusive community samples [23e41]. Forty-nine studies reported treatment for diabetes: participants used insulin only in four studies [19,42e44], oral agents only in seven [26,45e50], and in one study [51], diet was the only treatment. The remaining studies included mixed treatment modalities.…”
Section: Resultsmentioning
confidence: 99%
“…In 16 studies, participants were obtained from random or all-inclusive community samples [23e41]. Forty-nine studies reported treatment for diabetes: participants used insulin only in four studies [19,42e44], oral agents only in seven [26,45e50], and in one study [51], diet was the only treatment. The remaining studies included mixed treatment modalities.…”
Section: Resultsmentioning
confidence: 99%
“…2,[52][53][54][55] Characteristics of the study participants are shown in 32,38,46 and 11 pre-post-design studies. 3,7,8,19,21,22,29,30,36,37,40 These studies examined a wide range of interventions, including diabetes education and behavioral modification (15 studies), 3,7,8,21,22,32,39,40,42,43,45,[47][48][49][50] pharmacotherapy (11 studies), 19,20,26,28,31,[33][34][35][36]38,44 and surgery (7 studies). 27,29,30,37,41,46,…”
Section: Resultsmentioning
confidence: 99%
“…This improvement does not depend on the administration of sibutramine or placebo in combination with non-pharmacological treatments, but is directly related to weight loss and patients treated with sibutramine achieve more marked weight loss. More recently [24] , in a study on diabetic subjects treated with sibutramine or placebo, combined with comprehensive management, the authors were unable to show the expected QoL improvements despite the significantly greater weight loss observed in the sibutramine group. The authors suggest that factors other than weight loss per se influence the way patients rated their health-related QoL.…”
Section: Discussionmentioning
confidence: 99%